O movimento esportivo surdo: produções de modos de vida surda na contemporaneidade - Ferreira, Aline do Prado (2021)
This dissertation was developed through the Postgraduate Program in Education, in the line of research Special Education, Inclusion and Difference, and had as central objective to know and analyze the effects of the deaf sports movement in the production of deaf lifestyles in contemporary times. From the theoretical perspective of Cultural Studies and Deaf Studies and a post-structuralist perspective in education, the research approached an ethnographic-participatory approach for the production and analysis of materialities, being listed from them the following conceptual tools: subject (Michel Foucault); discourse (Michel Foucault); Representation (Stuart Hall). The materiality produced has offered a set of data collected through simple participant observation, recorded in a field diary and through an online questionnaire conducted with deaf leaders representing the deaf sports movement. Along the research, we have noticed the possibility of narrating deaf subjects beyond school or academic issues, showing a shift from the school context to deaf social life. Such displacement has pointed at the production of other representations about deaf lifestyles. From the conceptual tools listed, it was possible to notice the detachments from the representations of subjects with disabilities to subjects with culture, language and identity. Thus, the power of the deaf sports movement (Deaflympics) stands out to break with representations built on deaf people linked to sports.